Sergei Prokofiev’s violin concerto no. 1: exploring aspects of tone production, bowing, and left-hand technique - Coetzee, Zoe (Stellenbosch : Stellenbosch University, 2025)
Thesis (MMus)--Stellenbosch University, 2025.